Differential effect of two dietary protein sources on time course response of muscle anabolic signaling pathways in normal and insulin dysregulated horses - Loos, Caroline M. M.; McLeod, Kyle R.; Vanzant, Eric S.; Stratton, Sophie A.; Bohannan, Adam D.; Coleman, Robert J.; van Doorn, David A.; Urschel, Kristine L. (Frontiers in Veterinary Science, 2022)
The objective of the study was to characterize the temporal changes of phosphorylation patterns of mTOR signaling proteins in response to two dietary protein sources in insulin dysregulated (ID, n=8) and non-ID (n=8) horses. Horses were individually housed and fed timothy grass hay and 2 daily concentrate meals so that protein was the first limiting nutrient and the total diet provided 120 % of daily DE requirements for maintenance. On sample days, horses randomly received 0.25 g CP/kg BW of a pelleted alfalfa (AP) or commercial protein supplement (PS). Blood samples were collected before and 30, 60, 90, 120, 150, 180, 210, 240, 300, 360, 420 and 480 min post feeding and analyzed for plasma glucose, insulin and amino acid (AA) concentrations. Gluteus Medius muscle samples were obtained before and 90, 180 and 300 min after feeding and analyzed for relative abundance of phosphorylated mTOR pathway components using western immunoblot analysis. There was no effect of protein source on postprandial glucose and insulin responses (P≥0.14) but consumption of PS elicited a 2 times larger AUC for essential AA (EAA), greater peak concentrations of EAA and a shorter time to reach peak EAA concentrations compared to AP. Abundance of phosphorylated mTOR (P=0.08) and rpS6 ( P=0.10) tended to be ~1.5 fold greater after consumption of PS at 90 min compared to AP. Dephosphorylation patterns differed between protein sources and was slower for AP compared to PS. ID horses had a 2 times greater (P=0.009) AUC and 3 times higher postprandial peak concentrations (P<0.0001) for insulin compared to non-ID horses after consumption of both treatment pellets, but EAA responses were similar between groups (P=0.53). Insulin status did not affect rpS6 or mTOR phosphorylation after consumption of either protein source (P≥0.35), but phosphorylated rpS6 abundance was twice as high in ID compared to non-ID horses (P=0.007). These results suggest that consumption of higher quality protein sources may result in greater postprandial activation of the mTOR pathway compared to equal amounts of a forage-based protein source. Moreover, ID does not impair postprandial activation of mTOR and rpS6 proteins in horses following a protein-rich meal.